1997
DOI: 10.1111/j.1600-0714.1997.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of oral submucous fibrosis

Abstract: Oral submucous fibrosis (OSF) is a chronic disease of the oral cavity characterized by inflammation and progressive mucosal fibrosis. These reactions may be the result of either direct stimulation from exogenous antigens like areca alkaloids or by changes in tissue antigenicity that may lead to an autoimmune response. This study investigated the presence and distribution of inflammatory cells and MHC class II antigen expression by epithelial and immunocompetent cells using a three-stage immunoperoxidase method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 19 publications
8
41
0
Order By: Relevance
“…The increase in CD4 complement and cells with HLA-DR in OSF tissues suggests that most lymphocytes are activated and that the number of Langerhans cells increases. Haque et al (1997) studied subjects with OSF with immunohistochemical methods and found immunocompetent cells to be present in the lesion, with a high ratio of CD4 to CD8 cells. Therefore, they suggested an ongoing cellular immune response leading to a possible imbalance of immunoregulation with eventual local alterations in tissue architecture.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in CD4 complement and cells with HLA-DR in OSF tissues suggests that most lymphocytes are activated and that the number of Langerhans cells increases. Haque et al (1997) studied subjects with OSF with immunohistochemical methods and found immunocompetent cells to be present in the lesion, with a high ratio of CD4 to CD8 cells. Therefore, they suggested an ongoing cellular immune response leading to a possible imbalance of immunoregulation with eventual local alterations in tissue architecture.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer stimulating mechanisms operated by MCs include participation in immunosuppression, the release of proangiogenic and mitogenic factors and involvement in the degradation of the extracellular matrix. MCs contain many angiogenic factors and a variety of cytokines, such as histamine, heparin, tryptase, chymase, PDGF, TNF-α, bFGF, TGF-β, IL-6 and vascular endothelial growth factor (VEGF) [21].Upregulation of the above pro-angiogenic cytokines in OSF has already been demonstrated in the literature [22], [23], [24], [25], [62]. The present study demonstrated a statistically significant increase in subepithelial distribution of chymase positive MCs in OSCC group when compared to healthy controls and OSF group.…”
Section: Discussionmentioning
confidence: 95%
“…MCs are a major source of other pro-fibrotic cytokines like bFGF [15], TGF-β [20], [22], [23], IL-6 [47], and their upregulation has been studied extensively in OSF. Thus, we suggest that a combination of tryptase and chymase along with the various fibrogenic cytokines seems to be an important factor in the development of OSF (Figure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies have demonstrated that the submucosal fibrosis, oral leukoplakia, and oral erythroplakia that are commonly associated with betel quid, can impair a wide range of immune function parameters (Figure 1), which include but are not limited to: CD3 cells (T lymphocytes), CD4 cells (helper/inducer T lymphocytes), B lymphocytes, macrophages, 25 natural killer cells, 26 total leukocyte and lymphocyte counts, 27 immunoglobulin (Ig) G, IgM, and IgA, 28,29 circulating immune complex, 30 auto-antibodies such as gastric parietal cell antibody (GPCA), thyroid microsomal antibody, anti-nuclear antibody (ANA), anti-reticulin antibody, and anti-smooth muscle antibody (SMA). 31 Thus, under such a level of constant immunosuppression, it is biologically plausible that users experience an increased risk of opportunistic infection transmitted through other means (mosquito bite, food and drink, and risky sexual practices).…”
Section: Discussionmentioning
confidence: 99%